Houses as Lieux de Mémoire in Margery Allingham's Crime Fiction. (September 2021) - Zsámba, Renáta
Abstract : This article discusses the house as a site of memory in the novels of Margery Allingham, where it embodies a tension between the past and the present that turns the domestic milieu into a place of horror. Stemming from Susan Rowland's claim that Golden Age authors did not write 'unproblematically conservative country house mysteries' (43), this paper uses Svetlana Boym's theory of restorative and reflective nostalgia and Pierre Nora's concept of lieux de mémoire (sites of memory) to read Allingham's novels, which critically observe the sustainment of a vision of the past after the Great War. In her work, country houses like the eponymous one in The Crime at Black Dudley (1929), are, despite their aristocratic grandeur, perfect scenes for murder. While the countryside is associated with a nostalgic innocence, it is also contaminated by the intrusion of the present, as in Sweet Danger (1933). Family secrets are also reasons for crime, as we see in Police at the Funeral (1931). Hide My Eyes (1958) relocates the nostalgic atmosphere to a suburban house converted into a museum of 'curios', which operates as an ironic allegory of a nation wrapped up in its own history.